Deconstructing the Bakery to Build a Distributed State Machine. - LAMPORT, LESLIE (Communications of the ACM, 2022)
The article discusses two computer algorithms created by the author: the bakery algorithm which is based on mutual exclusion and the distributed state-machine algorithm which aims to achieve fault tolerance in a network of computers. Mathematical proofs are provided.